2005
DOI: 10.1210/jc.2004-0297
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Leptin Receptors and Potential Effects of Leptin on the Cell Growth and Activation of Mitogen-Activated Protein Kinases in Ovarian Cancer Cells

Abstract: Leptin, a secreted protein of the ob gene by white adipose tissue, plays an important role in the regulation of food intake and energy consumption in the brain and acts as a potential growth stimulator in normal and neoplastic breast cancer cells. However, a potential role of leptin as an endocrine regulator is unknown in ovarian cancer. In the present study, we investigated the expression of leptin receptors in immortalized ovarian surface epithelium (IOSE) and ovarian cancer cell lines, and potential effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 0 publications
5
88
0
2
Order By: Relevance
“…Previous reports have described a growth-stimulatory effect of leptin on gastric (Pai et al 2005), breast (Hu et al 2002, Stephenson & Rose 2003, Rose et al 2004, ovarian (Choi et al 2005) and prostate (Somasundar et al 2003) cancer cells. However, it inhibits the growth of pancreatic carcinoma (Somasundar et al 2003), suggesting a differential response of various cancer cells to leptin treatment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous reports have described a growth-stimulatory effect of leptin on gastric (Pai et al 2005), breast (Hu et al 2002, Stephenson & Rose 2003, Rose et al 2004, ovarian (Choi et al 2005) and prostate (Somasundar et al 2003) cancer cells. However, it inhibits the growth of pancreatic carcinoma (Somasundar et al 2003), suggesting a differential response of various cancer cells to leptin treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Both short and long isoforms of leptin receptors were observed in endometrial cancer cells, suggesting that leptin may be involved in endometrial cancer. In a recent report it was shown that not all ovarian cancer cell lines respond to leptin treatment, despite the presence of its receptors (Choi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although leptin has been viewed as the hormonal signal for the regulation of energy homoeostasis (Auwerx and Staels, 1998), several lines of evidence suggest that leptin plays a much broader physiological role (Rosenbaum and Leibel, 1999;Zhang et al, 2005). On a cellular level, leptin has been found to act as a metabolic regulator and motogenic and pro-angiogenic factors (Sierra-Honignann et al, 1998;Hardwick et al, 2001;Hu et al, 2002;Chio et al, 2004;Yin et al, 2004;Chen et al, 2006a). In addition, new evidence suggests that leptin could be involved in tumorigenesis, especially in the development of breast, colorectal and prostate cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data clearly indicate that the mitogenic, anti-apoptotic, proinflammatory and angiogenic properties of leptin promote the development and progression of different types of cancers (9). Several reports have described the mitogenic effects of leptin on gastric (10), breast (11), ovarian (12), prostate (13) and endometrial cancer cells (14). Two studies demonstrated that increased leptin levels are associated with greater risk of CRC development, particularly in males (15,16).…”
Section: Introductionmentioning
confidence: 99%